2022
DOI: 10.1111/pce.14378
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of seed glycerolipids in Asian cultivated rice

Abstract: Glycerolipids are essential for rice development and grain quality but its genetic regulation remains unknown. Here we report its genetic base using metabolitebased genome-wide association study and metabolite-based quantitative traits locus (QTL) analyses based on lipidomic profiles of seeds from 587 Asian cultivated rice accessions and 103 chromosomal segment substitution lines, respectively. We found that two genes encoding phosphatidylcholine (PC):diacylglycerol cholinephosphotransferase (OsLP1) and granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Genetic factors involved in variation for key metabolic traits have been successfully identified and characterized (i.e., primary and secondary metabolites and enzyme activities) (Wu et al, 2016(Wu et al, , 2018Fusari et al, 2017). A number of GWAS regarding lipid metabolism have been reported and resulted in the identification of new enzymes and regulators in species like Arabidopsis, maize, coffee, rice and canola (Riedelsheimer et al, 2013;Gacek et al, 2017;Sant'Ana et al, 2018;Li et al, 2019;Hong et al, 2022). These studies focused on lipid levels under optimal growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors involved in variation for key metabolic traits have been successfully identified and characterized (i.e., primary and secondary metabolites and enzyme activities) (Wu et al, 2016(Wu et al, , 2018Fusari et al, 2017). A number of GWAS regarding lipid metabolism have been reported and resulted in the identification of new enzymes and regulators in species like Arabidopsis, maize, coffee, rice and canola (Riedelsheimer et al, 2013;Gacek et al, 2017;Sant'Ana et al, 2018;Li et al, 2019;Hong et al, 2022). These studies focused on lipid levels under optimal growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, HAN1 (Mao et al, 2019) and COLD11 (Li, Zhang, Yang, et al, 2022) for chilling tolerance, OsALs (Alfin‐like family genes) for seed size and drought tolerance (Y. Yang, Ma, et al, 2022), OsLG3 (an ERF family TF) for drought tolerance (Xiong et al, 2018), DRO1 for saline tolerance (Kitomi et al, 2020), and NOMT (a naringenin 7‐O‐methyltransferase) for resistant to fungal diseases (Murata et al, 2020). In this issue, Hong, Rosental, et al (2023) profiled glycerolipids in seeds of 587 Asian cultivated rice accessions and 103 chromosomal segment substitution lines, and revealed their significant natural variation in rice. After mGWAS and mQTL analyses, they revealed that OsLP1 and Waxy are causal genes underlying natural variation in seed‐saturated triacylglycerol (TAG) and lyso‐phosphatidylcholine (lyso‐PC) contents, respectively.…”
Section: Natural Variations In Rice Resiliencementioning
confidence: 99%
“…After mGWAS and mQTL analyses, they revealed that OsLP1 and Waxy are causal genes underlying natural variation in seed‐saturated triacylglycerol (TAG) and lyso‐phosphatidylcholine (lyso‐PC) contents, respectively. Through combined population genetic analysis, they showed that natural variation in seed glycerolipids has been unconsciously shaped by natural (such as flooding and heading date) and artificial (such as taste) selection (Hong, Rosental, et al, 2023). The analyses of physiological effects of natural variation in seed glycerolipids are still ongoing in this group.…”
Section: Natural Variations In Rice Resiliencementioning
confidence: 99%
“…Plants were sown in a randomised complete block design (including two rows of each accession and eight plants in each row) (J. Hong et al, 2022). PH was measured using a ruler as the distance from ground to the top of the panicle at seed maturity (Yano et al, 2016).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The OsActin gene was used as an internal control to normalise the data using the comparative cycle threshold (ΔΔCt) method (J. Hong et al, 2022). Each experiment was repeated with three independent biological samples and three technical replicates.…”
Section: Expression Analysismentioning
confidence: 99%